2022
DOI: 10.1186/s12875-022-01654-6
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of primary care physicians towards initiation of phone consultations during the COVID-19 pandemic management in Qatar: a cross-sectional study

Abstract: Objectives To assess primary care physicians’ satisfaction towards initiation of phone consultation during COVID-19 pandemic management in Qatar and to identify the factors associated with dis/satisfaction. Design A cross-sectional web-based survey was conducted from 1 June to 30 July 2020. Setting All the available 27 public primary healthcare centers in Qatar at the time of the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…During the first wave of the pandemic, most countries experienced a rapid decrease in in-person medical consultations and an increase in remote consultations for primary and secondary care, with the majority of counseling sessions being conducted over the phone [ 13 ]. Neshnash et al found that during the Covid-19 pandemic, the use of telephone counseling in primary healthcare has been timely and effective, with more than half of primary care physicians being satisfied or very satisfied with the telephone consultations [ 86 ]. In fact, remote counseling improves access to primary care and enables general practitioners to see patients who require an in-person appointment more quickly [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the first wave of the pandemic, most countries experienced a rapid decrease in in-person medical consultations and an increase in remote consultations for primary and secondary care, with the majority of counseling sessions being conducted over the phone [ 13 ]. Neshnash et al found that during the Covid-19 pandemic, the use of telephone counseling in primary healthcare has been timely and effective, with more than half of primary care physicians being satisfied or very satisfied with the telephone consultations [ 86 ]. In fact, remote counseling improves access to primary care and enables general practitioners to see patients who require an in-person appointment more quickly [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neshnash et al found that during the Covid-19 pandemic, the use of telephone counseling in primary healthcare has been timely and effective, with more than half of primary care physicians being satisfied or very satisfied with the telephone consultations [ 86 ]. In fact, remote counseling improves access to primary care and enables general practitioners to see patients who require an in-person appointment more quickly [ 86 ]. Similarly, Green et al‘s study revealed that telephone counseling in the UK has nearly tripled from February 2020 to August 2021 [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased use of digital tools for communication has been seen during the pandemic, when digital inequalities may have been further reinforced by the lack of access to digital support [ 37 ], which is often limited in the home health care setting. Communication with patients digitally or by telephone was also described by the participants as a challenge, in contrast to a study of general physicians, who were satisfied with telephone consultations [ 38 ]. Digital tools can, however, be a challenge for older persons to use, even when they are the sole tool for social interaction, as during the pandemic [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the factors that need to be examined is the extent to which people in society use and benefit from the services, find them useful, and feel satisfied. A body of research examined the usage, usefulness, and satisfaction variables as perceived by people using technologies in the COVID-19 pandemic (29)(30)(31)(32)(33). However, few studies have examined the usefulness, satisfaction, and effectiveness of ehealth services provided by healthcare providers.…”
Section: Introductionmentioning
confidence: 99%